(untitled) (TEL Tempo, Espaço e Linguagem, 2026)
This article discusses the current restrictive laws governing access to healthcare for transgender children and adolescents, emphasizing the Brazilian context between 2023 and 2025. Drawing on ethnographic research and historiographic studies, I analyze: the effects these normative changes have produced in the practices of healthcare professionals and in adolescents’ lives; how the categories of “irreversibility,” “time,” and “linearity” operate in childhood and adolescent transgender experiences; and the ways in which medical knowledge assesses gender through “indices” and “rates” of “detransition” and “regret.” Finally, I speculate on the multiple meanings that “detransition” may carry when understood through bodily projects grounded in unpredictability.